모수적 부트스트랩을 이용한 차등정보보호 히스토그램의 동질성 검정 - 손주희; Juhee Son; 박민정; Min-jeong Park; 정성규; Sungkyu Jung (Ŭngyong tʻonggye yŏnʼgu, 2022)
본 논문에서는 모수적 부트스트랩을 이용한 두 차등정보보호 히스토그램의 동질성 검정을 제안한다. 제안된 검정 방법은 차등정보보호 히스토그램과 적용된 차등정보보호 수준 정보만 있을 때에도 사용 가능하며, 비교하고자 하는 두 히스토그램에 적용된 차등정보보호의 수준이 다를 때에도 사용할 수 있다는 장점이 있다. 검정 방법의 성능을 평가하기 위해 미국과 한국의 연령별 인구분포 자료를 사용하고, 제 1종 오류의 확률이 잘 통제됨과 높은 검정력을 확인한다. We propose a test of consistency for two differentially private histograms using parametric bootstrap. The test can be applied when the original raw histograms are not available but only the differentially private histograms and the privacy level α are available. We also extend the test for the case where the privacy levels are different for different histograms. The resident population data of Korea and U.S in year 2020 are used to demonstrate the efficacy of the proposed test procedure. The proposed test controls the type I error rate at the nominal level and has a high power, while a conventional test procedure fails. While the differential privacy framework formally controls the risk of privacy leakage, the utility of such framework is questionable. This work also suggests that the power of a carefully designed test may be a viable measure of utility.